Nutritional status assessment in colorectal cancer patients qualified to systemic treatment - Ziętarska, Monika; Krawczyk-Lipiec, Joanna; Kraj, Leszek; Zaucha, Renata; Małgorzewicz, Sylwia (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study . Cancer is usually associated with impaired nutritional status, which is one of the factors contributing to the deterioration of the results of surgery, chemotherapy, or radiotherapy. The aim of this study was the assessment of the nutritional status of patients with CRC qualified to chemotherapy. Material and methods : Seventy-five persons aged 40–86 years with colorectal cancer were examined. To evaluate the nutritional status NRS 2002, SGA, SCRINIO Working Group classification, VAS scale for appetite, and FAACT questionnaire were used. The health status of patients was evaluated based on the Karnofsky Performance Scale. Anthropometric measurements were made. Results : The results indicate that 75% of patients present pre-cachexia status based on SCRINIO Working Group classification. According to both NRS-2002 and SGA, 73.3% of patients were moderately malnourished and 2.7% were severely malnourished. 37.0% of patients had moderate appetite and 6.0% (n = 5) had poor appetite. The Karnofsky score indicates the state of normal activity, and minor signs and symptoms of the disease among most of the patients. A statistically significant positive correlation was found between the VAS and the Karnofsky score (R = 0,4; p < 0.05). The FACCT average score (78.5) indicates a reduction in the quality of life of the patients in all aspects of functioning. Conclusions : Evaluation of the baseline nutritional status of patients with CRC should be a part of routine clinical practice. Because of the high incidence of confirmed pre-cachexia, this group of patients also requires early adequate nutrition intervention.